DJ-1 deficiency causes metabolic abnormality in ornidazole-induced asthenozoospermia. Issue 6 (December 2020) - Sun, Yi; Sun, Xinping; Zhao, Lianming; Zhang, Zhe; Wang, Yupeng; Dai, Zhenfeng; Zhao, Xin; Pu, Xiaoping
Abstract : Asthenozoospermia (AS), defined as low-motility spermatozoa in the ejaculate, is a frequent cause of human male infertility. DJ-1 (also known as PARK7), a protein highly associated with male sterility, binds to the mitochondrial complex I subunit to protect mitochondrial function. However, its involvement in spermatogenesis has not been fully elucidated. Previously, the levels of DJ-1 were shown to be significantly decreased in testicular tissues of rats with ornidazole (ORN)-induced AS. Here, we used a rat model to investigate the localization and expression levels of DJ-1 and its interacting NDUFS3 and NDUFA4 mitochondrial complex I subunits, as well as AS-induced metabolic alterations in testicular tissues. ORN significantly reduced the levels of DJ-1 in the nucleus of secondary spermatocytes, while increasing the expression of NDUFS3 in the cytoplasm of primary spermatocytes. Further, NDUFA4 showed higher expression after treatment with ORN. The principal ORN-induced changes in metabolic small molecules related to the accumulation of glucose, glutamine, and N-acetyl aspartate, enhancement of purine pathway, increase of the phosphatidic acid (PA) (18:0/18:1), phosphatidylethanolamine (PE) (16:0/18:1), and PA (18:0/20:4) lipid metabolites, and imbalance in the concentrations of Na + and K + . However, we did not observe any abnormalities of certain small metabolic molecules and metal ions in semen samples from patients with AS. In conclusion, these results suggest that DJ-1 deficiency in testicular tissues might be closely related to the localization of NDUFS3 and content of NDUFA4, thus causing abnormalities in the mitochondrial energy metabolism and multiple other metabolic pathways.